Faktor-Faktor yang Menentukan Permintaan Buah Lokal pada Hotel Berbintang di Kota Denpasar dan Kabupaten Badung - SUMAWIDARI, IAK.; PUTRA DARMAWAN, DWI; SRI ASTITI, N W. (JURNAL MANAJEMEN AGRIBISNIS; Vol. 1, No. 1, Mei 2013, 2014)
Bali is one of the tourist destinations in Indonesia, where there are three priority factors on Bali development. They are agriculture, tourism with its culture and Hindu religion and home industry to support agriculture and tourism sector. The rapid development in tourism sector is expected that the holticulture product especially local fruits could be accommodated by tourism industry especially the big or star hotels which most of them located at Badung Regency. But in this free trade globalization, imported fruits products spreading in Bali are as a tight competitors in order to be able market segment especially to the star hotels in Bali. The title of this research, the dominand factors for the demand of local fruits at star hotels in Badung Regency. The choice of this location is done by using purposive sampling. The purpose of this research are : (1) To identify the fruits needed at star hotels in Badung Regency. (2) To know the factors for demand of local fruits at star hotels in Badung Regency, and (3) To know the deminand factor for the demand of local fruits at star hotels in Badung Regency. The samples taken are 96 hotels by using the Proportionate Stratified Random Sampling Technique. The data are collected by using (1) observation, (2) interview, (3) questionnaire and (4) documented method. There are 18 fixed variable indicators and they are analized by using inductive statistic. It is factor of analizes.  The result this research shows that : (1) There 10 kinds of fruits needed by the star hotels in Badung Regency such as : watermelon, melon, pineapple, papaya (popo), king banana, snakeskin fruit, kapok banana, gold banana, red apple and avocado. (2) There are 5 factors for local fruits demand at star hotels in Badung Regency. They are : the quality of the fruit, the price, hotel policy, continuation and government policy. (3) From those 5 factors available, exactly the quality of the fruits is as dominant factors to influence the demand of local fruits at the star hotels in Badung Regency.  From the result of this research could be suggested for : (1) Farmers. They should develop their knowledge and skill for planting local fruit plantations by joining agriculture information through both newspaper and electronically. (2) The supplier should have commitment to local fruits by doing more marketing to the star hotels in Bali especially in Badung Regency. (3) The government should give more agricultural information to the farmers and also to provide superior quality of the seed which are needed by the farmers and more tight policy for the imported fruits.
Keywords: demand, local fruit, star hotel.